Surface runoff estimation in an upper watershed using geo-spatial based soil conservation service-curve number method - C.A. Odiji; O.M. Aderoju; M.C. Ekwe; D.T. Oje; J.O. Imhanfidon (Global Journal of Environmental Science and Management, 2020)
Runoff assessment and estimation is crucial for watershed management as it provides information that is needed to expedite the course of watershed planning and development. The most commonly used model due to its simplicity and versatility in runoff estimation is the soil conservation service curve number developed by the United States Department of Agriculture. The study estimates the surface runoff of Upper Benue watershed using a geospatial based soil conservation service curve number model. Datasets utilized for this purpose are; Rainfall, land use, digitial elevation model and FAO-Soil. The soil and land use data were intersected to create the curve number grid and database. The curve number grid combined with the mean annual rainfall data from 1990 – 2017 was used to estimate runoff. The result revealed that 61.5% of rainfall was direct runoff while 38.5% of the rainfall was retained by tree/plant cover and soil. The average curve number for the normal condition was calculated to be 80.1 while the dry and wet season was 59.6, and 93.2 respectively. The average runoff volume for 27 years was estimated to be 69,887.43mm3. A correlation coefficient of 0.79 was found for the relationship between rainfall and runoff. The research highlights the importance of geospatial technique when integrated with soil conservation service curve number to estimate runoff conditions in Upper Benue Watershed.